Compliance of Resilient Denture Liners Immersed in Effervescent Denture Cleansers - Douglas G. Benting, DDS, MS;1 Igor J. Pesun, DMD, MS;2 (Journal of Prosthodontics, 2005)
Six resilient denture liners (RDL) were exposed to two immersion effervescent denture cleansers to evaluate change in compliance over a simulated 1 year time interval.